Long-term effects of peginterferon alfa-2a therapy in Japanese patients with chronic hepatitis B virus infection - Masaki, Keiichi (Virol J, 2015)
BACKGROUND: There is no information on the long-term effects of peginterferon (PEG-IFN) alfa-2a therapy for chronic hepatitis B (CHB) in Japan. This double-blind, randomized trial investigated the efficacy of PEG-IFN therapy. METHODS: We analyzed 22 Japanese patients with CHB (hepatitis B e antigen [HBeAg]-positive: 17, HBeAg-negative: 5) treated with PEG-IFN alfa-2a and followed-up posttreatment for 5 years. Responders represented patients who showed persistent normalization of alanine transferase (ALT) levels, HBeAg clearance, and low hepatitis B virus (HBV) DNA levels (HBeAg-positive patient; <5 log copies/mL, HBeAg-negative patient; <4.3 log copies/mL) at end of treatment, and at 1, 2, 3, 4 and 5 years posttreatment. In addition, baseline HBeAg-positive patients who showed sustained normalization of ALT level, HBeAg clearance, and low HBV DNA level for more than 6 months until at 1, 2, 3, 4, and 5 years after completion of PEG-IFN were also classified as “triple responders” and the proportion of triple responders relative to all patients was termed the “triple response rate”. RESULTS: The response rates among HBeAg-positive patients were 13 %, 25 %, 14 %, 21 % and 21 % at end of treatment, and at 1, 2, 3, 4, and 5 years, respectively. The response rate tended to be higher in patients treated for 48 than 24 weeks. The respective response rates among HBeAg-negative patients were 0 %, 20 %, 20 %, 20 % and 25 %. During the treatment period, hepatitis B surface antigen (HBsAg) clearance at 3.5 years was noted in one patient, who was 37-year-old, male, had genotype C and received PEG-IFN alfa-2a at 90 μg for 48 weeks. CONCLUSION: At 5 years after completion of PEG-IFN, the triple response rate in HBeAg-positive patients and combined response rate in HBeAg-negative patients were 21 % (3/14) and 25 % (1/4), respectively. The triple response was seen in three patients who had all been treated with PEG-IFN for 48 weeks.